FDM models and FEA in dysplastic hip - Dhakshyani, R.; Nukman, Y.; Azuan, A.N. (2012)
Purpose - The purpose of this paper is to examine the use of fused deposition modelling (FDM) models and finite element analysis (FEA) related to dysplastic hip orthopaedic surgery. Design/methodology/approach - The study involved the use of Mimics and Abaqus softwares. Mimics was used to process the CT scan patient data to STL format before producing FDM models which were for before and after surgery. FEA was done to study the two different type of implant biomaterials used in dysplastic hip surgery. Findings - The use of FDM pre models for preplanning of dysplastic hip surgery by orthopaedic surgeons and viewing of the surgery outcome via FDM post models. Different implant biomaterials used gave different results in reduction of stresses that were achieved. Originality/value - This is original work involving patients in hospital, which got ethical approval and was funded by a university grant. The paper describes a new kind of research in the university.